(untitled) (Acta Entomologica Serbica, 2023)
Caliaeschna microstigma is a species distributed mainly in the eastern Mediterranean, from Croatia in the west to northern Iran and Caucasus in the east. Until this study, it was reported only from a few localities in Serbia, which are located in far south. Here we have summarized all available data and presented new data on the distribution of C. microstigma in Serbia. The Eastern Spectre was detected at seven new localities (four during field study and three from publicly available databases), extending its current range in Serbia by more than 120 km to the north.